2012
DOI: 10.1080/1351847x.2012.712920
|View full text |Cite
|
Sign up to set email alerts
|

Wealth effects of convertible-bond and warrant-bond offerings: a meta-analysis

Abstract: Abstract:We review the literature on wealth effects associated with the announcements of convertible bond and warrant-bond offerings. The findings of 35 event studies, which include 84 sub-samples and 6,310 announcements, are analysed using meta-analysis. We find a mean cumulative abnormal return of -1.14% for convertibles compared with -0.02% for warrant-bonds, the significant difference confirming a relative advantage for warrantbonds. Abnormal returns for hybrid securities issued in the United States are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Other studies compare the differences of stock market reactions upon convertible bond offerings among different industries find mixed results. For example Suchard (2007) finds that convertible bond issues by Australian industrial firms are associated with more negative abnormal return than resource firms (mineral and energy sectors), while Abdul Rahim et al (2014) find no significant difference between industrial and non-industrial companies in their meta-analysis.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies compare the differences of stock market reactions upon convertible bond offerings among different industries find mixed results. For example Suchard (2007) finds that convertible bond issues by Australian industrial firms are associated with more negative abnormal return than resource firms (mineral and energy sectors), while Abdul Rahim et al (2014) find no significant difference between industrial and non-industrial companies in their meta-analysis.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In the metaanalysis of wealth effects of convertible bond offerings by Abdul Rahim, Goodacre, and Veld (2014), most studies in their samples either eliminate financial institutions because they have different considerations when choosing capital structure compared to non-financial institutions or include financial institutions without differentiating them from the nonfinancials. Studies in general have found that non-financials experience significant negative abnormal stock returns (e.g., Abhyankar & Dunning, 1999;Ammann, Fehr, & Seiz, 2006;Burlacu, 2000;De Jong et al, 2012;Duca, Dutordoir, Veld, & Verwijmeren, 2012;Murphy, Kleimain, & Nathan, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The overwhelming evidence shows a negative post-issuance valuation effect (Abhyankar and Dunning 1999;Agarwal et al 2011;Bechmann 2004;Carpentier, L'Her, and Suret 2013;Chou et al 2009;Duca et al 2012;Lewis, Rogalski, and Seward 2001;Lin et al 2013;Rahim, Goodacre, and Veld 2014;Zeidler, Mietzner, and Schiereck 2012). Rahim, Goodacre, and Veld (2014) conducted a meta study of 35 studies across 84 samples and 6,310 announcements and found a negative wealth effect of 1.14%; US issuances of convertibles were associated with more negative wealth effects (an additional 1.11%). The most representative and highly cited study is a paper by Hillion and Vermaelen (2004) who reported that floating rate convertibles result in significantly negative post-issuance abnormal returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jinn (2011) argues that, when firms have an underinvestment problem and cannot raise money in the public markets due to the adverse selection problem despite their growth opportunities, BW issuance in the form of private placements may positively affect firm value. Rahim et al (2014) report that BW issuance positively affects firm value due to the tax effect for profitable firms. However, other studies claim that BW issuance affects firm value negatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, the empirical literature on the wealth effects of the announcements of CBs and BWs is abundant, but the results are mixed across countries (Rahim et al 2014). Studies in the US report significantly larger negative abnormal returns for both CBs and BWs than for those issued in other countries (Billingsley et al 1990;Lewis et al 2003).…”
Section: Literature Reviewmentioning
confidence: 99%